PERLINDUNGAN HUKUM TERHADAP PERUSAHAAN FACTOR DALAM PENAGIHAN PIUTANG DAGANG PADA TRANSAKSI ANJAK PIUTANG (FACTORING) - Dwi Mayasari, I Dewa Ayu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 2 (2015), 2015)
Research in connection with jurnal writing thesis takes the theme the protection of the law against companies factor in billing accounts receivable factoring transactions. Problems studied involves two things; the first what factors the company’s legal position as a buyer on receivables in factoring and financing institution both what form of legal protection that can be given to companies factor of a possible failure of the trade receivables collection. This includes research conducted legal research categories, namely normative legal research literature or legal research based on secondary data. The approach used is the approach ot the laws and facts approach. Next to for further analysis techniques use the description legal interpretation techniques based argumentative theory, principles, and concepts relevan laws. The results showed that the company,s legal position as a purchaser of  factoring receivables is very weak and vulnerable than risk the possibility of failure of collection of accounts receivable due to non fulfillment of the achievements by the customer. In this context there is no guarantee of  legal protection for the company for the payment or refund factor its receivables in full. The next from legal protection that can be given to the factor as a buyer of receivables is; a) apply the type of recourse factoring in the factoring agreement with the burden of responsibility is on the client in case of failure of collection of accounts receivable, b) implement a system of personal/corporate guarantees, and c) apply the prudential banking principles
Keywords: Standing; Legal Protection; Client; Company Factor; Factoring